MENGGALI POTENSI MASYARAKAT DALAM MENGHADAPI PESAING MELALUI EDUKASI MANAJEMEN STRATEGI DI PASAR TRADISIONAL KEC. KOTAGAJAH - Rahyono, Rahyono; Wuryanti, Lestari; Lukman, Iing; Harun, Harmani (Jurnal Bakti Masyarakat Manajemen, 2024)
One of the strategies in dealing with competitors is to take advantage of the potential of the community and renew the way of trading by using the latest strategies that are in accordance with the conditions in the current era. This service aims to provide knowledge and skills to traders in the Traditional Market, Kotagajah sub-district, Central Lampung in maximizing the potential of the community through marketing strategy education through strategic management intended to deal with outside competitors. This service provides knowledge to participants who attend, especially traders, to use the best strategy to increase sales. This service is carried out in the Kotagajah sub-district multipurpose building and at the Kotagajah traditional market, the method used is to provide training material through presentations accompanied by management implementation training. strategy. The achievement of this dedication was the implementation of strategic management training which was attended by regional apparatus of Kota Gajah, members of youth organizations, and women farmer groups.